Introduction: Special Issue on Adolescents in the Majority World. (14th February 2013) - Raffaelli, Marcela; Lazarevic, Vanja; Koller, Silvia H.; Nsamenang, A. Bame; Sharma, Deepali
<x xml:space="preserve">Abstract</x> This special issue showcases research on the 90% of the world's adolescents growing up in the "majority world" (i.e., Asia, Africa, Latin America and the Caribbean). Articles were solicited that addressed three focal areas by (1) evaluating existing developmental models or proposing culturally based approaches to studying adolescent development; (2) describing successful models of interventions to improve the well‐being of youth; and (3) examining how global factors are experienced locally by adolescents. Contributors address these themes in a range of adolescent populations from majority world nations. We hope this special issue will be a useful resource to scholars who conduct research and teach about adolescence, to practitioners working with adolescents from different national backgrounds, and policymakers working on international issues.